2021
DOI: 10.1007/s10639-021-10613-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of usability on the intention to use the e-learning system in a sustainable way: A case study at Universitas Indonesia

Abstract: E-Learning has been massively used in higher education, one of which is in Universitas Indonesia. The e-learning system in Universitas Indonesia is called Student Centered E-Learning Environment Universitas Indonesia (SCELE UI). This research determines the effect of usability on the intention to use SCELE UI in a sustainable way. The Expectation Confirmation Model (ECM) is used as a basis of the research model. Perceived Usability, Learnability, Presentation, Navigation and Error variables are added to the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 115 publications
(197 reference statements)
1
18
0
2
Order By: Relevance
“…In other research, Thong, Hong, and Tam also found that the perceived usefulness of mobile internet services has a significant effect on adult user satisfaction [18]. This is also aligned to the statement from [21], if technology can help users improve their performance, then the technology is felt to be useful [22]. From these statements, a hypothesis is proposed to find out how the perceived usefulness of MOOCs affects user satisfaction.…”
Section: Satisfactionsupporting
confidence: 56%
“…In other research, Thong, Hong, and Tam also found that the perceived usefulness of mobile internet services has a significant effect on adult user satisfaction [18]. This is also aligned to the statement from [21], if technology can help users improve their performance, then the technology is felt to be useful [22]. From these statements, a hypothesis is proposed to find out how the perceived usefulness of MOOCs affects user satisfaction.…”
Section: Satisfactionsupporting
confidence: 56%
“…Perceived usefulness (β = 0.593, p < 0.001) significantly impacted continuance intention [ 54 56 ]. Satisfaction (β = 0.397, p < 0.001) significantly impacted continuance intention [ 14 , 57 , 58 ]. Perceived usefulness (β = 0.317, p < 0.001) significantly affected satisfaction [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the ECM, users will be satisfied with an information system if they confirm their expectations (Zuo et al, 2021). Prior studies in online learning also demonstrated that confirmation is positively associated with users' satisfaction (Lee, 2010;Persada et al, 2021;Ramadhan et al, 2022). As such, this study proposed that:…”
Section: Expectation-confirmation Modelmentioning
confidence: 94%
“…This study aims to bridge this gap by investigating the factors affecting Chinese college students’ continued intention of using online learning from a theoretical perspective. Considering that the Expectation-Confirmation Model (ECM) has become the most applied theory to explain individuals’ usage behaviors of various information communication technologies ( Ramadhan et al, 2022 ), this study employs the ECM as the theoretical underpinning to examine how ECM factors (i.e., confirmation, perceived usefulness, perceived enjoyment, and satisfaction) are related to university students’ intention to continue learning online. However, other factors can also affect people’s behavioral intention toward the adoption of information technologies, such as the opinions of prominent individuals (subjective norms; Fishbein and Ajzen, 1975 ).…”
Section: Introductionmentioning
confidence: 99%